Human Development in Times of Extraordinary Events: Study on the Effect of Government Spending, Unemployment Rate, and Pandemic Severity on the Human Development Index During the Covid-19 Pandemic - Ayu, Siti Nur (Universitas Pamulang, 2025)
This research aims to look at human development during extraordinary events as seen from the influence of government spending, especially in health and education spending by local government, unemployment rates, and the severity of the Covid-19 pandemic that occurred. Population data uses data from all provinces in Indonesia from 2020 to 2022. Analysis of the development and condition of HDI, government spending, unemployment levels, and the severity of the pandemic using descriptive statistical methods. Meanwhile, to determine the development and extent of the effect of government spending variables, unemployment levels, and the severity of the pandemic on human development, this research uses panel data regression analysis with the Fixed Effect Model (FEM). Panel data analysis findings indicate that government spending variables in the education and health sectors have no bearing on raising the HDI score. However, the HDI is significantly impacted by the unemployment rate and the pandemic's severity. Based on these findings, this study suggests that government expenditure in the health and education sectors be optimized to deal with extraordinary events and maintain the region's focus on human development growth.